A New Record and а Taxonomic Review with Checklist of Wolf Spiders (Araneae, Lycosidae) from Iraq - Al-Yacoub, G. A. A.; Najim, S. A. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2023)
The material in the present study was collected from two agricultural regions in Thi-Qar and Basrah Provinces, southern Iraq. Pardosa roscai (Roewer, 1951) was recorded for the first time from Thi Qar Province in Iraq. А list of wolf spiders (Araneae: Lycosidae) from Iraq is presented. In addition, a map of the areas, with a taxonomic review and confirmation of five species of wolf spiders is given, with photographs of palp and epigyne of several species, which were not published in previous studies.